THE EFFECT OF OVERLOAD ON THE DESIGN OF LIFE OF ROAD PAVEMENT (CASE STUDY: KOTI ROAD, JAYAPURA CITY) - Kurnia Hadi Putra; Ita Suhermin Ingsih; Theresia Maria Candra Agusdini; Mila Kusuma Wardani; Felicia Tria Nuciferani; Muhammad Exchel Cakra Putra (Journal Innovation of Civil Engineering (JICE), 2023)
The roads hold a vital role in the transportation system in the Province of Papua, especially in the Jayapura area. However, real road conditions often experience a decrease in performance (damage) due to construction failures or deviant utilization. On Koti Road in Jayapura, sometimes vehicles passing it do not match the maximum permissible load. Consequently, excessive loading on the pavement can directly affect the design life of a road section. Therefore, this study aims to analyze the percentages of actual overload on each vehicle class, the increase in the cumulative VDF value, and the decrease in the design life on Koti Road, Jayapura. The research results indicated that the actual overload on Koti Road, Jayapura, obtained 81.06% for group 6a, 43.13% for group 6b, and 40.42% for group 7a. According to the Bina Marga method (1987), the cumulative VDF value increased by 133.8% due to actual excessive load in the field, while based on the NAASRA method (2004), it was 121.2%. In terms of the actual overload effects, the design life decreased by 9,273 years, or 46,365%, from the 20-year design life using the Bina Marga (1987) method, while based on the NAASRA (2004) method, the decrease in design life was 8.7898 years, or 43.949%, from the 20-year life plan. Keywords: Importance Performance Analysis; Facility Feasibility; Field Show Terminal